Handbook of industrial and hazardous wastes treatment - Wang, Lawrence K. (Marcel Dekker, Inc., 2004)
Presenting effective, practicable strategies modeled from ultramodern technologies and framed by the critical insights of 78 field experts, this vastly expanded Second Edition offers more than 20 chapters of industry- and waste-specific analyses and treatment methods for industrial and hazardous waste materials - from explosive wastes to landfill leachate to wastes produced by the pharmaceutical and food industries. Key additional chapters cover means of monitoring waste on site, pollution prevention, and site remediation.
Revised edition of: Handbook of industrial waste treatment. c1992.
Keywords: Factory and trade waste -- Management.; Industries -- Environmental aspects.; elektronické knihy; electronic books